Oxidized low density lipoprotein receptor 1 promotes lung metastases of osteosarcomas through regulating the epithelial-mesenchymal transition - Long Jiang (Journal of Translational Medicine, 2019)
Abstract Background Oxidized low density lipoprotein receptor 1 (OLR1), a type II membrane protein, has been identified as receptor for oxidized low-density lipoprotein. The current study firstly provided evidence that OLR1 regulated EMT and thus promoted lung metastases in osteosarcoma (OS). Method All relevant experiments were conducted according to the manufacturer’s protocols. In vivo tumor xenograft experiments were carried out in 6- to 16-week-old mice, then maintained in our animal facility under pathogen-free conditions in accordance with the Institutional Guidelines and approval by local authorities. For the use of the clinical materials for research purposes, prior patient’s consent and approval from the Institute Research Ethics Committee were obtained. All statistical analyses were performed using IBM SPSS Statistics 22.0 for Windows. Result Microarrays were adopted to explore the underlying epigenetic mechanisms related to metastasis. 11 genes were identified among total 26,890 differentially expressed genes. After validated in paired primary and metastatic tissues, OLR1 was selected in the current study. The expression levels of OLR1 were tested in 4 widely used cell lines. Cell proliferation, migration and invasion could be enhanced when OLR1 was overexpressed. OLR1 overexpression also triggered G1 to S + G2 phases of cell cycle. Accordingly, cell proliferations, migration and invasion would be reduced when OLR1 was silenced. OLR1-silencing blocked G1 to S + G2 phases of cell cycle. Also, OLR1 silencing effectively suppressed local tumor carcinogenesis and lung metastases in vivo. Moreover, silencing OLR1 repressed the expression of mesenchymal markers (Snail, Twist, and N-cadherin), but induced an epithelial marker (E-cadherin). Conclusion This study indicated a novel molecular mechanism involving the role of OLR1 in lung metastases of osteosarcoma, strengthened the correlation between OLR1 and lung metastases.